Effect of COVID-19 on Energy Sector in Jordan - Myyas, Ra’ed Nahar; Almajali, Mohammad R. (International Journal of Energy Economics and Policy, 2022)
This study aims to analyze the impact of the COVID-19 on the energy sector in Jordan. The steps taken by the Jordanian governments to mitigate the economic and financial impacts that would enhance the resilience of the energy sector was considered. Deductive and inductive analysis methods of were used. Such methods aided to systematically consider the economic consequences of the COVID-19. The results of this study showed that the COVID-19 led to a significant decrease in energy consumption, a decline in economic growth, a significant rise in unemployment, an increase in market instability, and a decrease in the financial position of companies. The recommendations concluded that Jordan should begin to change its policies according to the new data, and take Measures to advance the energy sector by reducing fuel consumption and directing investment in energy saving policies and infrastructure equipment in parallel with the population boom in Jordan.